Embodied inner human being - Weissenrieder, Annette; Etzelmüller, Gregor (Religion & theology, 2014)
In this paper we take issue with George H. van Kooten’s recent argument that Paul’s concept of inner human being has a background in ancient philosophical treatises as a metaphor of the soul. We argue that its Greco-Roman physiological meaning was decisive in its adoption by Paul and that the split between ancient medicine and philosophy was not essential in antiquity. Ancient medical-philosophical texts did not focus on the core or center of a person but rather sought a deep understanding of his or her inner aspects. These texts sought to understand how it is that we can discover bodily information about this inner person and to what degree the relationship between the inner and outer person can be interpreted. At the same time, however, we are discussing Walter Burkert’s evolutionary understanding of Pauline’s concept of the inner and outer human being. Paul’s definition of the inner human being corresponds to recent anthropological concepts of embodiment insofar as the visible outer human being has an inside which, according to Paul, is not detached from the body, but must be grasped from a physical perspective.